Antioxidant and Antisenescence Effects of Bergamot Juice. (12th July 2018) - Da Pozzo, Eleonora; De Leo, Marinella; Faraone, Immacolata; Milella, Luigi; Cavallini, Chiara; Piragine, Eugenia; Testai, Lara; Calderone, Vincenzo; Pistelli, Luisa; Braca, Alessandra; Martini, Claudia
Abstract : Aging is one of the main risk factor for the onset of cardiovascular diseases; one of the possible explanations could be linked to the age-associated overproduction of free radicals. This increase of oxidative stress can be overcome with a high intake of food antioxidants. In this context, a number of studies have been addressed to assess the antiaging potential of natural antioxidant compounds. Recently, it has been shown that the juice of bergamot ( Citrus bergamia Risso et Poiteau), a fruit mostly produced in the Ionian coastal areas of Southern Italy (Calabria), is a valuable source of health-promoting constituents with, among other, antioxidant properties. In order to investigate the potential antiaging effects of this Mediterranean natural antioxidant source, bergamot juices of three different cultivars ("fantastico, " "femminello, " and "castagnaro") were herein characterized by the mean of high-performance liquid chromatography-photodiode array-electrospray ionization-tandem mass spectrometry. Then, juices were investigated for the evaluation of total polyphenolic and flavonoid contents, cell-free model antioxidant activities, and in vitro antiaging properties on two different cellular models of induced myocardial senescence. The best performing juice was also assessed in vivo . The phytochemical profiles confirmed that juices were rich in flavonoids, both flavone and flavanone glycosides. In addition, two limonoid glycosides were also identified in all cultivars. Each cultivar showed different phenolic and flavonoid contents. In tube results showed the juice robust antioxidant activities that correlate with their phenolic and flavonoid contents. Moreover, for the first time, the ability of juice to counteract the chemical-induced senescence was here demonstrated in both cellular models. Lastly, the in vivo data obtained from mouse hearts evidenced an increase in transcription of genes involved in antiaging and antioxidant responses. The overall results suggest that bergamot juice exerts antioxidant and antisenescence effects, making it useful for nutraceutical purposes.